2013
DOI: 10.1016/j.bbmt.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Soluble Form of Tim-3 Associated with Severe Graft-versus-Host Disease

Abstract: The T cell Ig and mucin domain 3 (Tim-3) receptor has been implicated as a negative regulator of adaptive immune responses. We have utilized a proteomic strategy to identify novel proteins associated with graft versus host disease (GVHD) after allogeneic hematopoietic cell transplantation (HCT). Mass spectrometry analysis of plasma from subjects with mid-gut and upper-gut GVHD compared with those without GVHD identified increased levels of a protein identified with high confidence as Tim-3. A follow-up validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 49 publications
5
54
0
Order By: Relevance
“…Analysis of inflammatory cytokines and markers of inflammation across time (Figure 4) suggests that most allograft recipients experience significant systemic inflammation to day 100. Our findings are consistent with recent studies that have identified TNFR1 and ST2 as useful biomarkers for more severe GVHD 2,7-9 but that are inconsistent with regard to REG3a11 (which was less predictive than other analytes) and TIM3 12 (which was more predictive). Despite the statistically significant operating characteristics of the analytes that we have identified in predicting more severe GVHD and NRM, the use of these data in clinical trials designed to improve outcomes is likely to encounter difficulties.…”
Section: Blood 2 July 2015 X Volume 126 Number 1 Acute Gvhd Biomarksupporting
confidence: 90%
See 2 more Smart Citations
“…Analysis of inflammatory cytokines and markers of inflammation across time (Figure 4) suggests that most allograft recipients experience significant systemic inflammation to day 100. Our findings are consistent with recent studies that have identified TNFR1 and ST2 as useful biomarkers for more severe GVHD 2,7-9 but that are inconsistent with regard to REG3a11 (which was less predictive than other analytes) and TIM3 12 (which was more predictive). Despite the statistically significant operating characteristics of the analytes that we have identified in predicting more severe GVHD and NRM, the use of these data in clinical trials designed to improve outcomes is likely to encounter difficulties.…”
Section: Blood 2 July 2015 X Volume 126 Number 1 Acute Gvhd Biomarksupporting
confidence: 90%
“…The Luminex microbead method (Luminex, Austin, TX) was used for measurement of 21 analytes, as previously described. 12 A sandwich enzyme-linked immunosorbent assay method was used for transforming growth factor-b1 and REG3a, as previously described. 17 Supplemental Table 1 lists the reagents used in these assays along with their respective lower levels of detection.…”
Section: Collection and Processing Of Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further characterization of this protein suggested a role in inhibiting T cell responses to tumor antigen in vitro and in vivo (31). Using mass spectrometry, Hansen et al first discovered a Tim-3 construct in human plasma which was found to be associated with graft-versus-host disease (32). However, this plasma Tim-3 construct is poorly characterized, and it is unclear whether this soluble Tim-3 is elevated in chronic infections such as HIV.…”
mentioning
confidence: 99%
“…Thus, it is unclear which construct, the alternatively spliced or the membrane-cleaved sTim-3, represents the sTim-3 form found in human plasma. Furthermore, while sTim-3 has been correlated with graft-versus-host disease (32), it is unknown whether it can modulate immune pathways. Given Tim-3's role in HIV-associated T cell dysfunction (12)(13)(14), sTim-3 might play a role in modulating T cell responses during HIV infection.…”
mentioning
confidence: 99%